48th AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2012
DOI: 10.2514/6.2012-3870
|View full text |Cite
|
Sign up to set email alerts
|

Ion Current Density Study of the NASA-300M and NASA-457Mv2 Hall Thrusters

Abstract: NASA Glenn Research Center is developing a Hall thruster in the 15-50 kW range to support future NASA missions. As a part of the process, the performance and plume characteristics of the NASA-300M, a 20-kW Hall thruster, and the NASA-457Mv2, a 50-kW Hall thruster, were evaluated. The collected data will be used to improve the fidelity of the JPL modeling tool, Hall2De, which will then be used to aid the design of the 15-50 kW Hall thruster. This paper gives a detailed overview of the Faraday probe portion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…And the integrated beam current densities for the NASA-457M v2 thruster operating at a discharge current and voltage of 100 A and 200 V, respectively, showed that beam ion currents were indeed higher during high magnetic field operation (Ref. 20). However, even though the laboratory model thruster operating with high magnetic fields likely produced a higher ion beam current for discharge currents  60 A as shown in Figure 7, the thrust was still less than or equal to that of the v2 thruster at lower magnetic fields as shown in Figure 6.…”
Section: Lab Modelmentioning
confidence: 99%
“…And the integrated beam current densities for the NASA-457M v2 thruster operating at a discharge current and voltage of 100 A and 200 V, respectively, showed that beam ion currents were indeed higher during high magnetic field operation (Ref. 20). However, even though the laboratory model thruster operating with high magnetic fields likely produced a higher ion beam current for discharge currents  60 A as shown in Figure 7, the thrust was still less than or equal to that of the v2 thruster at lower magnetic fields as shown in Figure 6.…”
Section: Lab Modelmentioning
confidence: 99%
“…The near-field Faraday probe is not discussed here as it is the primary subject of a companion paper. 5 The probe array used is similar to one used in a previous study on the NASA-300M. 4 Figure 1 shows photographs of the probe array both before and during operation.…”
Section: Near-field Plume Diagnosticsmentioning
confidence: 99%
“…This trend is confirmed with ion current density measurements made in the near-field at these conditions. 5 Comparisons between the two measured sides of the thruster as well as further discussions regarding the acceleration zone can be found in Section IV. Figure 9 shows the contour maps of measured electron temperature downstream of the exit plane at four operating conditions.…”
Section: A Plasma Potentialmentioning
confidence: 99%
See 2 more Smart Citations